Biosorbent Prepared from Calotropis Gigantean Stems for Adsorption of Cu(II) Ions from Aqueous Solution - Husna, Asmaul; Abdullah, Faisal; Muslim, Abrar; Suhendrayatna, Suhendrayatna; Meilina, Hesti (Jurnal Rekayasa Kimia & Lingkungan, 2021)
Calotropis gigantea stems (CGS) has the potential to use as biosorbent for adsorption of Cu(II) ions. In this study, the CGS biosorbent (CGSB) was prepared by drying and grounding. The effect of independent variables on adsorption capacity were investigated. As the result, the maximum adsorption capacity of 53.457 mg/g was obtained the optimal condition which was initial Cu(II) ions concentration of 567.47 mg/L, CGSB size of less than 230 mesh, CGSB mass of 1 g, temperature of 27 oC, pH 5, and contact time of 60 min. The CGSB surface morphology was analysed using SEM. The adsorption of Cu(II) ions fitted well with pseudo first-order adsorption kinetic (PFO-AK) model (R2=0.99), and the PFO-AK adsorption capacity and rate constant obtained were 70.194 mg/g and 0.0877 g/mg.min, respectively. The adsorption isotherm of Cu(II) ions was in accordance with Freundlich model (R2=0.99), and the intensity and volume constants attained were 0.876 and 1.017 L/mg, respectively. This result showed that physical adsorption occurred dominantly than chemical adsorption. The application of CGSB on the wastewater of initial Cu(II) ions concentration of 389.31 mg/L from ex-mine pool of acid mine drainage (AMD) in Jantang village, Lhoong District, Aceh Besar, Aceh Province resulted in adsorption capacity of 37.52 mg/g with adsorption efficiency of 66.13%.